Implementation of Ex Officio Rights of Judges of the Kediri District Religious Court: An Analysis of Non-Cumulation of Divorce and Child Custody Rights - Muhammad Al Pani; Sholehuddin, Miftahus; Safia Niaz, Noorjehan (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2023)
This research highlights the phenomenon that occurred in the Kediri Regency Religious Court regarding the cumulation of lawsuits, it was found that there were still many parties who filed a pure lawsuit without filing a lawsuit in cumulation. The parties often only focus on the divorce lawsuit without including aspects regarding child custody, which can be cumulated according to Article 86 paragraph (1) of Law No.7 of 1989 concerning Religious Courts. The focus of this research is to find out why the parties do not cumulate the divorce lawsuit with child custody and the implementation of the ex officio rights of the judge of the Kediri Regency Religious Court. The research method used is juridical-empirical with a sociological juridical approach. Primary and secondary data were obtained through interviews and documentation. The results of the study concluded that some of the reasons the parties did not cumulate the lawsuit with child custody included ignorance of the parties regarding the cumulation of the lawsuit, the role of legal counsel, the existence of a prior agreement, focus on divorce priorities. Judges of the Kediri Regency Religious Court have applied the applicability of ex officio rights as a privilege owned by judges to impose decisions aimed at providing benefits, namely the fulfillment of the rights of those concerned. Judges can use ex officio rights in divorce cases to give the wife and children their rights such as iddah, mut'ah, madhiyah, and child maintenance. Judges cannot exercise ex officio rights in a contested divorce and cannot impose a decision that is not in the argument of the lawsuit such as a case regarding child custody because of Ultra Petitum Partium.